Fluid Power Control for Sun tracking of Solar panels: Modelling and Simulation - Ahmed ABU HANIEH (International Journal of Applied Methods in Electronics and Computers, 2016)
This paper focuses on discussing a hydro-pneumatic hybrid (Gas/Oil), passive technique for sun tracking and orientation of solar panels, collectors and food dryers. The technique depends on utilizing the natural expansion of gases caused by temperature increase. The pressure produced by gas expansion causes a force exerted on hydraulic oil contained in the same vessel with the gas and separated from it by a diaphragm. Hydraulic fluid is used here for the stroke control because of its advantage over gas in terms of incompressibility and controllability.  The exerted force caused a 50 mm displacement of the actuator which can be improved by decreasing the bore diameter of the piston and by using gases with higher expansion coefficient.